Keeping it Close to Home: Changes in Regional Trading Patterns - Jackson, Paul (The Ohio State University, 2014)
I examine the implications of protectionist trade policy imposed by a large open economy like the United States on the behavior of regional trading patterns of a small open economy like Thailand and Philippines. I find that the direction of trade for Thailand and Philippines has shifted from the United States to Asia in the last twenty years. Despite this trend, I do not find a connection between this direction of trade shift and the implementation of protectionist policy. As an alternative explanation, I use difference-in-differences estimations to show that the formation of the North Atlantic Free Trade Agreement (NAFTA) can help explain the direction of trade shift and leave this paper to future research into the implications of the formation of regional free trade agreements. No embargo Academic Major: Economics